Review of studies on risk allocation and sharing in public-private partnership projects for infrastructure delivery - Mazher, Khwaja Mateen (Frontiers in Built Environment, 2025)
Public–private partnerships (PPPs) continue to grow globally as a means of procuring essential infrastructure and services to meet the ever-increasing demands of rising population and enhanced service delivery standards. Adequate risk allocation and sharing (RAS) is considered a critical success factor in PPP project delivery, however, it is exceptionally complex to establish and structure, difficult to monitor, and demands effort to properly enforce it in PPP contracts. This study aims to systematically review the existing PPP research in the RAS domain to explore the status quo, trends, and gaps in research. A thorough search and a meticulous shortlisting of academic literature resulted in 80 relevant journal articles published since the start of the 21st century whereafter a systematic content analysis was performed on these articles. Frequency analysis showed that nearly half of the reviewed papers were published by three journals including the journal of construction engineering and management, international journal of project management and construction management and economics journal. Furthermore, China and Australia seem to be the most active contributors accounting for 42 articles. Researchers extensively relied on case studies, literature review and surveys among other research methodologies for RAS research. The review further categorized the articles in five subcategories for in depth analysis. Most of the research reviewed falls in the “risks allocation and sharing preferences, practices, and models” category and accounts for 49% of the journal articles reviewed whereas the second largest category “government support and guarantees” accounts for 29% of the articles reviewed. Several research gaps were identified, and it is hoped that the results will motivate future research and enhance the body of knowledge in the domain of RAS in PPPs.